Karl Marx - Rowcroft, Andrew (Abingdon, Oxon ; New York, NY : Routledge, 2021)
Karl Marx is the most important modern philosopher. His work has radically changed the course of world history, continental philosophy, political theory, literary criticism, and cultural studies. The sheer range of his achievements, and the depth of his critical insights, continue to speak to our present moment. This book places Marx's writings in their historical context, providing a clear guide to his key ideas and intellectual legacy. Written for both students and scholars, it illustrates Marx's ideas with examples drawn from William Shakespeare, Herman Melville, Leo Tolstoy, Bertolt Brecht, Theodor Dreiser, Thomas Pynchon, Toni Morrison, Sally Rooney, Claude McKay, Tennessee Williams, Mad Men, and Margin Call. Key ideas discussed in this guide include: Tracing historical contexts and developments in Marx's work over his lifetime Focusing on Marxism as an interpretative strategy, paying special attention to its impact on literary criticism and cultural studies Examining recent developments in Marxist theory, such as a stronger focus on the environment, climate crisis, and world ecology Exploring the continued relevance of Marx and Marxism today. This Routledge Critical Thinkers guide will enable readers to critically assess and interpret Marx's major works, while also introducing his methods of critical analysis. Preparing readers to approach his original texts, this guide ensures that readers of all levels will find Marx accessible, challenging, and of continued relevance. Andrew Rowcroft offers a comprehensive introduction to Marx's revolutionary ideas, examining the influence Marx had on literary studies, cultural studies, modernism, and philosophy.
OCLC-licensed vendor bibliographic record.
Keywords: Marx, Karl, -- 1818-1883.; Philosophy, Marxist; Communism; Philosophers -- Germany -- Biography; LITERARY CRITICISM / General